Governance and innovation (Journal of Economic Additions, 2020)
Governance is a central process given its prestigious position, because it is a selection tool, then its creation as a final form in the field of management decisions, and its transcendence is linked to an exclusive recourse to identification. primary variables, whose objective is economic, and with a more institutional face, gives the greatest importance to the newly created entities, with their presence within a structure requires to meet regulations that include rigor and specialization, in which the social, cultural or even political reality becomes revolving axes of follow-up, in parallel with what happens of universal change, with a notable speed, where the objective is a standard of living, and the conditions of existence which include popular demands, Its benchmarks are linked to social comparisons, exist at an internal or external level, and also contribute to the transmission of all processes over current secretions, to focus on a holistic level, through which Competitions are opened, making them determined by a level of creativity and experienceKey words: governance- innovation - experience- investigation- criticismJel Classification Codes: Q31، Q32